Identifikasi Ergonomi Postur Kerja dengan Metode Nordyc Body Map (NBM) dan Rapid Entire Body Assessment (Reba) di UMKM Mandiri Furnitur Pasuruan: Maulidatul Masudha, Enik Sulistyowati, Rizky Stighfarrinata - Maulidatul Masudha; Enik, Sulistyowati; rizky, stighfarrinata (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
Work-related injuries are a potential risk, including in aluminum cutting activities within UMKM producing household goods made from aluminum and glass. Assessing ergonomic postures is crucial to prevent Musculoskeletal Disorders (MSDs). This study utilized the Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) methods to analyze posture data. NBM focuses on identifying ergonomic variables affecting posture, while REBA evaluates the injury risk level of specific postures. The findings show that combining NBM and REBA effectively identifies high-risk postures with accuracy and highlights which body parts require follow-up. This approach proves to be effective in enhancing occupational health and safety. Applying these methods helps business owners detect and minimize ergonomic risks, contributing to improved worker safety, comfort, and well-being.